Comparison of endothelial promoter efficiency and specificity in mice reveals a subset of Pdgfb‐positive hematopoietic cells. (24th March 2019) - Kilani, Badr; Gourdou‐Latyszenok, Virginie; Guy, Alexandre; Bats, Marie‐Lise; Peghaire, Claire; Parrens, Marie; Renault, Marie‐Ange; Duplàa, Cecile; Villeval, Jean‐Luc; Rautou, Pierre‐Emmanuel; Couffinhal, Thierry; James, Chloe
Abstract : Essentials To reliably study the respective roles of blood and endothelial cells in hemostasis, mouse models with a strong and specific endothelial expression of the Cre recombinase are needed. Using mT/mG reporter mice and conditional JAK2 V617F/WT mice, we compared Pdgfb‐iCreERT2 and Cdh5(PAC)‐CreERT2 with well‐characterized Tie2‐Cre mice. Comparison of recombination efficiency and specificity towards blood lineage reveals major differences between endothelial transgenic mice. Cre‐mediated recombination occurs in a small number of adult hematopoietic stem cells in Pdgfb‐iCreERT2;JAK2 V617F/WT transgenic mice. Summary: Background: The vessel wall, and particularly blood endothelial cells (BECs), are intensively studied to better understand hemostasis and target thrombosis. To understand the specific role of BECs, it is important to have mouse models that allow specific and homogeneous expression of genes of interest in all BEC beds without concomitant expression in blood cells. Inducible Pdgfb‐iCreERT2 and Cdh5(PAC)‐CreERT2 transgenic mice are widely used for BEC targeting. However, issues remain in terms of recombination efficiency and specificity regarding hematopoietic cells. Objectives: To determine which mouse model to choose when strong expression of a transgene is required in adult BECs from various organs, without concomitant expression in hematopoietic cells. Methods: Using mT/mG reporter mice to measure recombination efficiency and conditional JAK2 V617F/ WT mice to assess specificity regarding hematopoietic cells, we compared Pdgfb‐iCreERT2 and Cdh5(PAC)‐CreERT2 with well‐characterized Tie2‐Cre mice. Results: Adult Cdh5(PAC)‐CreERT2 mice are endothelial specific but require a dose of 10 mg of tamoxifen to allow constant Cre expression. Pdgfb‐iCreERT2 mice injected with 5 mg of tamoxifen are appropriate for most endothelial research fields except liver studies, as hepatic sinusoid ECs are not recombined. Surprisingly, 2 months after induction of Cre‐mediated recombination, all Pdgfb‐iCreERT2;JAK2 V617F/ WT mice developed a myeloproliferative neoplasm that is related to the presence of JAK2V617F in hematopoietic cells, showing for the first time that Cre‐mediated recombination occurs in a small number of adult hematopoietic stem cells in Pdgfb‐iCreERT2 transgenic mice. Conclusion: This study provides useful guidelines for choosing the best mouse line to study the role of BECs in hemostasis and thrombosis.